Russian Classics in Translations into Latin as Part of “Fundamentals of the Latin Language” Course - D. V. Kiryukhin (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to translations of Russian classics into Latin, made by A. N. Kuryashkin and Yu. A. Stasyuk, and how they can be used in the classes for the Latin language in higher educational institutions of Russia. The author notes that the Latin language does not lose its importance today, remaining one of the most important subjects for philologists, historians and philosophers who need to work with the primary sources, as well as for doctors and veterinarians whose professional activity is impossible without the skills of reading, translating and writing clinical and anatomical terms and recipes. Translations of classic poetic works of M. V. Lomonosov, A. S. Pushkin, M. Yu. Lermontov, K. I. Chukovsky, A. L. Barto and other authors, of course, familiar to students from school, as well as the well-known Russian songs can be used by the teacher not only as texts for the training of oral reading and translation, but also as part of the additional and creative tasks. In addition, it is possible to include them in the number of control questions to the test (exam), which should arouse students’ interest, motivation and form skills of independent analysis of the text.